1998
DOI: 10.1111/j.1095-8649.1998.tb01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal grazing rates and food processing by tropical herbivorous fishes

Abstract: Seasonal variability in grazing rates and food-processing characters were assessed for three abundant fishes in a tropical rocky shore: the damselfish Stegastes fuscus, the parrotfish Sparisoma atomarium, and the surgeonfish Acanthurus bahianus. Significant differences were found in grazing rates among hour of day and seasons, and in food-processing characters among seasons for the three fishes. Grazing rates for S. atomarium and A. bahianus peaked at 1300 and 1400 hours for S. fuscus. Three main periods of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 23 publications
1
60
0
Order By: Relevance
“…Our results corroborate previous results about the existence of another major abundant component which also dominates large portions of the reef substratum on the study site, together with Palythoa, the epilithic algal community (EAC) (Ferreira et al 1998a(Ferreira et al , b, 2001. The EAC in the study site and in rock shores of Arraial do Cabo in general was dominated by red articulate coralline algae (Amphiroa and Jania), and red and green filamentous (Ceramium, Polysiphonia, Cladophora).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate previous results about the existence of another major abundant component which also dominates large portions of the reef substratum on the study site, together with Palythoa, the epilithic algal community (EAC) (Ferreira et al 1998a(Ferreira et al , b, 2001. The EAC in the study site and in rock shores of Arraial do Cabo in general was dominated by red articulate coralline algae (Amphiroa and Jania), and red and green filamentous (Ceramium, Polysiphonia, Cladophora).…”
Section: Discussionsupporting
confidence: 92%
“…The distribution and composition of benthic communities along the Brazilian coast are strongly correlated with general environmental and geographical variables (Lana et al 1996, Ferreira et al 2004. With more than 8,000 km of coast extension, a diverse scenario provides different ecological processes which generate diverse communities and trophodynamics processes (Kempf 1970, Eston et al 1986, Rosa and Moura 1997, Ferreira et al 1998a, b, Reis and Yoneshigue-Valentin 1998. Despite this, few studies investigated the vertical distribution and the influence of benthic communities and complexity on reef fishes (Ornellas and Coutinho 1998, Floeter et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the same studied area, Ferreira et al (1998Ferreira et al ( , 2001Ferreira et al ( , 2004 concluded that the greater probability of disturbance of filamentous algae on Cabo Frio Island is due to fish herbivory, which might have resulted in a probability of disturbance approximately twice that of the upper side of the panels. The herbivorous fish Stephanolepis hispidus (Actinopterygii, Monacanthidae) was commonly observed cleaning the panels (personal observation) that was re-colonized by filamentous algae, thus initiating a continuous successional process.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies about the community ecology of Brazilian reef fishes began in the late 1990s, and applied underwater visual census techniques (Rosa & Moura, 1997;Rocha et al, 1998;Ferreira et al, 1998;Rocha & Rosa, 2001). These studies were conducted at several sites throughout the tropical and subtropical Brazilian coastline, from below the mouth of the Amazon River at the Manuel Luiz Reefs (0 o 52' S) (Rocha & Rosa, 2001), to the south to Santa Catarina State (27 o 30' S) .…”
Section: Introductionmentioning
confidence: 99%